Smart Technologies. SmartTech-IC 2022: Third International Conference on Smart Technologies, Systems and Applications - Contreras Urgilés, Rafael Wilmer (2023)
This book contains the papers presented on poster sessions at the Third International Conference on Smart Technologies, Systems and Applications (SmartTech-IC 2022) held on November 16-18, 2022 in Cuenca, Ecuador. The SmartTech-IC conference aims to attract researchers, scientists and technologists from some of the top companies, universities, research groups, and government agencies from Latin America and around of the world to communicate their research results, inventions and innovative applications in the area of smart science and the most recent smart technological trends. SmartTech-IC 2022 was organized by the Universidad Politécnica Salesiana, a private institution of higher education with social purposes, nonprofit and co-financed from the Ecuadorian State. The SmartTech-IC conference has been conceived as an academic platform to promote the creation of technical and scientific collaboration networks. The goal of the conference was addressed some relevant topics related to smart technologies, smart systems, smart trends and applications in different domains in the field of computer science and information systems that represent innovation in current society.